Structural and magnetic properties of Ni0.5Zn0.5Fe2O4 synthesized through the sol-gel method - Guan, B.H. (Trans Tech Publications Ltd, 2014)
This study investigates the influence of calcination temperatures on the magnetic properties of Ni0.5Zn0.5Fe2O4(Ni-Zn) ferrites.Ni-Zn ferrite with the chemical formula Ni0.5Zn0.5Fe2O4 was prepared from their respective nitrate salts through the sol-gel method. The resulting ferrites were characterized using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and vibrating sample magnetometer (VSM). Single phased Ni0.5Zn0.5Fe2O4 was obtained at all calcination temperatures.FESEM Micrographs reveals an increase in the grain size with the increase of the calcination temperature. Consequently, the magnetic saturation of the samples were found to increase with each increase in the calcinations temperature where the highest value obtained is 70.58 emu/g for the samples calcined at 1000Â°C. Â© (2014) Trans Tech Publications, Switzerland.